OGC P07 A Preoperative Predictive Tool to Assess the Need for Staging Laparoscopy in Oesophagogastric Cancer Patients. (7th December 2022) - Halle-Smith, James; Bage, Timothy; Kamarajah, Sivesh; Pande, Rupaly; Whiting, John; Griffiths, Ewen
Abstract: Background: Staging laparoscopy (SL) has become commonplace in the preoperative staging pathway for oesophagogastric (OG) cancer due to the tendency for peritoneal carcinomatosis (PC) to be present, which may be macroscopic peritoneal metastases (PM) or positive peritoneal cytology (PPC). The aim of this study was to develop an objective risk scoring system to predict both PM and PPC at SL. Methods: A prospectively collected and maintained database of all OG cancer patients treated between 2006-2020 was reviewed. Univariate and multivariate analyses were performed to identify risk factors for both PM and PPC at SL. A risk score was then produced for both PM and PPC, then internally validated. Results: Amongst 968 patients who underwent SL, 96 (9.9%) patients had PM and 81 (8.4%) had PPC at SL. Tumour site (p<0.001), CT T stage (p<0.001) and N stage (p=0.029) were significantly associated with PM at SL. (p<0.001). Tumour site (p<0.001), biopsy histology (p=0.041) CT T stage (p<0.001) and N stage (p<0.001) were significantly associated with PPC. The risk scoring model for PM included cancer site and CT T stage. This was successfully tested on the validation set (AUROC = 0.730). The risk scoring model for PPC included cancer site, CT T and N stage. This was successfully tested on the validation set (AUROC = 0.773). Conclusions: The present risk scores are valid tools with which to predict the risk PM and PPC in patients undergoing SL for OG cancer and may help to avoid subjecting patients to unnecessary SL.